Cognitive style and Computer-Assisted Learning: problems and a possible solution - John A. Clarke (Association for Learning Technology, 1993)
Although the notion of cognitive style has been around for some time, only in relatively recent times has there been a research interest in examining its effect on the performance of Computer-Assisted Learning (CAL) users. There are a number of practical difficulties associated with catering for different cognitive styles of CAL users. This paper identifies not only a style which influences CAL-user performance and overcomes many of the difficulties, but also a possible suitable measure of that style. Data on the reliability of this measure is reported, along with preliminary work on its use to cater for CAL users with different cognitive styles. Future work will focus on the development of the package and the predictive validity of the style measure.